Doświadczanie świata muzyki przez dziecko w kontekście wymagań podstawy programowej edukacji wczesnoszkolnej - Majzner, Rafał (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
This article attempts to analyze the recommendations contained in the current core curriculum relating to the various forms of experiencing the world by children at early school age. On this basis, the author of the study formulates proposals concerning the forms of experiencing the world of music by a child that are not included in the school’s curricula, but are necessary for the full and harmonious development of children.
Keywords: aesthetic experience of music; child; experiencing music; music